Long-term deep decarbonisation pathways for Ecuador: Insights from an integrated assessment model. (May 2021) - Villamar, Daniel; Soria, Rafael; Rochedo, Pedro; Szklo, Alexandre; Imperio, Mariana; Carvajal, Pablo; Schaeffer, Roberto
Abstract: This work presents an Integrated Assessment Model (IAM) developed for Ecuador, the so-called Ecuador Land Use and Energy Network Analysis model (ELENA). This model includes six distinctive sectors of the economy and displays the four geographic regions composing the country. The model enables to capture sectorial interactions, under a set of scenarios designed to evaluate the energy and land perspectives until 2050. The model is a crucial planning instrument to evaluate public policies, such as National Determined Contributions (NDC) and even more ambitious decarbonisation scenarios. Findings show that Ecuador's NDC are not aligned with the "well below" 2 °C target, committed in the Paris Agreement. Moreover, to achieve deep decarbonisation it is necessary to endorse disruptive strategies in which bioenergy and reforestation play a main role. To keep under the 1.5 °C temperature threshold above pre-industrial levels, Ecuador's energy matrix must be diversified with higher shares of low carbon technologies and electrification of energy end use in the transport, buildings and industry sectors. Biomass with carbon capture and storage (BECCS) and biofuels could transform the energy sector in a CO2 sink. Highlights: Ecuador Land Use and Energy Network Analysis model assess Energy and Land trade-offs. Ecuador needs an integrated long-term strategy to comply with Paris Agreement goals. Ecuadorian National Determined Contributions lack of long-term strategies. Bioenergy with carbon capture and storage could be the key of a low carbon emission future. Reforestation is an alternative to costly and non-mature carbon capture and storage technologies.